Estado democrático de direito e Poder Judiciário: as audiências públicas no Supremo Tribunal Federal e a legitimidade das decisões judiciais - Leandro, Paulo Cesar Cavasin (2015)
The discussion about the institutional role of the Judiciary Branch on a Democratic Rule of Law has been running on a singular way because the global expansion of its intervention on political questions in. This scenario shows a possible paradox, whereas for the majority countries with Roman-Germanic judge tradition, the lack of representative legitimacy (by the vote) to decide about political questions for the Judiciary Branch is a reality. In Brazil, the phenomenon either appears, and it shows that much more traditional questions hasbeen discussed in the Legislature Branch seat and are taken for the STF appreciation. With this basal knowledge, , this work has two main objecitves: the first is to analyze theoretically the role of the politic evolution in the Judicial Branch, on the political organization of Rule of and the Democrat Rule Of Law paradigms, comparing what happened in Brazil and the central european countries. After that, we did a qualitative analyze about public heraings as a way of democrartic legitimation for contitucional jurisdictional activities. Starting by the theorical mark of the “Discourse Principle”, told by Habbermas, we looked for the transition of the way of the political – legal organization of the Democratic Rule of Law, both in theory and in the Brazilian case. We present the institutional role of the STF in the Brazilian Democratic Rule of Law and make a deep research about the public hearings that were within the constitutional jurisdiction. In the end, we concluded that the achievement of public hearings only make an important role in the legitimation (or validation) enforcement of the rights when they are taken on a serious way by the STF Ministers, turning possible to the people who are involved to join on the reasonable speech that gave for the judges the base for the decision.